On dogs, people, and a rabies epidemic: results from a sociocultural study in Bali, Indonesia - Widyastuti, M.D.W.; Bardosh, K.L.; Sunandar; Basri, C.; Basuno, E.; Jatikusumah, A.; Arief, R.A.; Putra, A.A.G.; Rukmantara, A.; Estoepangestie, A.T.S.; Willyanto, I.; Natakesuma, I.K.G.; et al. (Springer, 2015)
Background Previously free of rabies, Bali experienced an outbreak in 2008, which has since caused a large number of human fatalities. In response, both mass dog culling and vaccination have been implemented. In order to assess potential community-driven interventions for optimizing rabies control, we conducted a study exploring the relationship between dogs, rabies, and the Balinese community. The objectives of this study were to: i) understand the human-dog relationship in Bali; ii) explore local knowledge, attitudes, and practices (KAPs) relating to rabies; and iii) assess potential community-driven activities to optimize rabies control and surveillance. Methods Conducted between February and June 2011, the study combined a questionnaire (n = 300; CI = 95 %; error margin = 5 %) and focus group discussions (FGDs) in 10 villages in the Denpasar, Gianyar, and Karangasem regencies. The questionnaire included a Likert scale to assess community knowledge and attitudes. For the knowledge assessment, three points were given for a correct answer, while wrong answers and uncertain answers were given zero points. For the attitudes assessment, three points were given for a positive answer, two points for a neutral answer, and one point for a negative answer. Respondent knowledge was categorized as good (score >40), fair (score 20–40), or poor (score <20), based on a maximum total score 60. Respondent attitudes were categorized as positive (score >26), neutral (score 13–26), or negative (score <13), based on a maximum total score of 39. Mixed-gender FGDs in each sub-village (banjar) were conducted, each involving 7–15 participants to complement the questionnaire results. On a follow-up research trip in mid-2013, the data analysis was triangulated and validated using semi-structured interviews. Questionnaire data were analyzed descriptively using SPSS 17.0, while qualitative data from interviews and FGDs were analyzed manually according to accepted methods of coding and memo writing. The chi-square test was then used to analyze the statistical relationships between knowledge and attitudes of the respondents. Results Out of the total 300 respondents, most were predominantly male (82 %), Hindu (99 %), married (96 %), older than 30 years of age (92 %), and owned dogs (72 %). Dog ownership was motivated by culture, personal taste, and function, with dogs was being used as guards (85 %) and companion animals (27 %), and was sometimes related to religious or traditional obligations (2 %). Relating to their culture and local beliefs, and eventually becoming their way of life, 79 % of respondents kept free-roaming dogs. With the rabies outbreak in Bali and Western breeds becoming more popular, more responsible dog ownership (leashing, confining, regular feeding) became more acceptable and changed community perceptions on keeping dogs, even though the sustainability of this practice cannot be gauged. In addition, the economic situation posed major problems in rural areas. The level of community knowledge about rabies and its associated control programs were generally fair and community attitudes were positive. However, community KAPs still need to be improved. A total of 74 % respondents reported to have vaccinated their dogs in 2011, but only few were found to report rabid animals to livestock officers (12 %) and a significant number believed that washing a bite wound was not important (62 %). Moreover, free-roaming dog practices and discarding of unwanted female puppies still continue and possibly create difficulties for rabies elimination as these practices potentially increase the stray dog population. We identified three major sociocultural aspects with potential for community-driven interventions to optimize current rabies elimination efforts: integrating local notions of ahimsa (non-violence) into education campaigns, engaging communities through the local banjar sociopolitical system, and working with traditional legal structures to increase local compliance with rabies control. Conclusion The human-dog relationship in Bali is multifaceted. Due to the uniqueness of the culture and the local beliefs, and encouraged by a socioeconomic aspect, a number of local practices were found to be constituting risk factors for continued rabies spread. Community knowledge and attitudes, which can consequently result in behavioral changes, needs to be improved across different genders, ages, educational backgrounds, and roles in the community, regardless of the individual village’s experiences with rabies. Furthermore, community-driven activities based on sociocultural conditioning and community capacity at the banjar and village levels, such as public awareness activities, vaccination, dog registration, dog population management, and rapid response to dog bites, were identified as being able to complement the rabies control program in Bali. The program also needs recognition or acknowledgement from governments, especially local government as well as regular mentoring to improve and sustain community participation.